(untitled) (Bangladesh Medical Journal, 2016)
High-dose methotrexate (HDMTX) therapy is an effective therapy for childhood ALL, which is frequently associated with side effects like infection in our centre. It prolongs hospital stay, delays chemotherapy and causes more economic burden on patients.This study was done to identify the incidence, risk factors and severity of infection among children with ALL during HDMTX therapy.This prospective observational study was conducted among 50 patients suffering from acute lymphoblastic leukemiascheduled to receive HDMTX at the Department of Pediatric Hemato-oncology of BSMMU. It was carried out from January 2012 to June 2012.The end result showed, 19 (38%) patients su_ered from infection; among them microbiologically documented infections found in 9 occasions, where gram negative bacilli - E.coli 4(44.4%) & Pseudomonas 3(33.33%) were predominant organisms. Gastrointestinal tract (GIT) was the most common site (8,42.11%).The rate of infection is significantly higher in children <5 yrs(78.94%). Mortality rate was 6%. As the infection and case fatality rate is quite high with HDMTX therapy, we recommend to use this drug with caution. Bangladesh Med J. 2016 Jan; 45 (1): 6-13